The Influence Of Labor Recruitment, Entrepreneurship Training, Entrepreneurial Orientation, And Organizational Innovation On The Performance Of Entrepreneurs With Entrepreneurial Commitment As The Intervening Variable - Yanita Yanita (Green Publisher Indonesia, 2022)
This research examined and analyzed the performance of embroidery entrepreneurs in Aceh in five regencies consisting of embroidery entrepreneurs in Banda Aceh, Aceh Besar, Bireun, Lhokseumawe, and West Aceh. The sampling method used was Proportional Stratified Sampling, which then carried out random sampling in each city or district and obtained 198 embroidery entrepreneurs. This research used AMOS Structural Equation Model (SEM) as a tool for data analysis. The results revealed that Labor Recruitment, Entrepreneurship Training, and Entrepreneurial Orientation positively influenced Entrepreneurial Commitment and Entrepreneur Performance. Meanwhile, organizational innovation had no positive influence on entrepreneurial commitment and Entrepreneur performance. The entrepreneurial commitment acted out as the intervening variable mediated the relationship between labor recruitment and Entrepreneur Performance (Fully Mediated). The entrepreneurial commitment did not act as an intervening variable and did not mediate the relationship between entrepreneurial training and Entrepreneur Performance (Partially Mediated). The entrepreneurial commitment did not act as an intervening variable and did not mediate the relationship between entrepreneurial orientation and Entrepreneur Performance (Partially Mediated). The entrepreneurial commitment did not act as an intervening variable and did not mediate the relationship between